Correlation of Serum Cystatin C with Glomerular Filtration Rate in Patients Receiving Platinum-Based Chemotherapy. (18th December 2016) - Cavalcanti, Ernesta; Barchiesi, Vittoria; Cerasuolo, Dionigio; Di Paola, Flaviano; Cantile, Monica; Cecere, Sabrina Chiara; Pignata, Sandro; Morabito, Alessandro; Costanzo, Raffaele; Di Maio, Massimo; Perrone, Francesco
Abstract : Objectives . Serum cystatin C seems to be an accurate marker of glomerular filtration rate (GFR) compared to serum creatinine. The aim of this work was to explore the possibility of using serum cystatin C instead of serum creatinine to early predict renal failure in cancer patients who received platinum based chemotherapy. Design and Methods . Serum creatinine, serum cystatin C concentrations, and GFR were determined simultaneously in 52 cancer patients received carboplatin-based or cisplatin-based chemotherapy. Serum creatinine was assayed on Cobas C6000-Roche, serum cystatin C assay was performed on AIA 360-Tosoh, and GFR was determined in all patients, before the first cycle of chemotherapy and before the subsequent administrations. Results . In the overall series, for the prediction of a fall of GFR < 80 mL/min/1.73 m 2, the AUC of the ROC curve for cystatin C was 0, 667 and the best threshold was 1.135 mg/L (sensitivity 90.5%, specificity 61.1%). For a GFR fall < 60 mL/min/1.73 m 2, the AUC of ROC curve for cystatin C was 74.3% and the best threshold was 1.415 mg/L (sensitivity 66.7%, specificity 73.2%). Conclusions . Baseline cystatin C values were not able to predict renal failure during subsequent treatment. In conclusion, serum cystatin C is not a reliable early marker to efficiently predict renal failure in patients receiving chemotherapy.